Agent-Based Modeling Approach of Immune Defense Against Spores of Opportunistic Human Pathogenic Fungi - Tokarski, Christian; Hummert, Sabine; Mech, Franziska; Figge, Marc Thilo; Germerodt, Sebastian; Schroeter, Anja; Schuster, Stefan (Frontiers in Microbiology, 2012)
Opportunistic human pathogenic fungi like the ubiquitous fungus Aspergillus fumigatus are a major threat to immunocompromised patients. An impaired immune system renders the body vulnerable to inva- sive mycoses that often lead to the death of the patient. While the number of immunocompromised patients is rising with medical progress, the process and dynamics of defence against invaded and ready to germinate fungal conidia are still insufﬁciently understood. Besides macrophages, neutrophil granulocytes form an important line of defence in that they clear conidia. Live imaging shows the interaction of those phagocytes and conidia as a dynamic process of touching, drag- ging and phagocytosis. To unravel strategies of phagocytes on the hunt for conidia an agent-based modeling approach is used, implemented in NetLogo. Different modes of movement of phagocytes are tested regard- ing their clearing efﬁciency: random walk, short term persistence in their recent direction, chemotaxis of chemokines excreted by conidia and communication between phagocytes.